A stable polymeric chain configuration producing high performance PEBAX-1657 membranes for CO2 separation. Issue 7 (30th May 2019) - Sharma, Pankaj; Kim, Young-Jin; Kim, Min-Zy; Alam, Syed Fakhar; Cho, Churl Hee
Abstract : By improving the polymeric structure and reforming the free-volume of pristine PEBAX films, the permeability, as well as CO2 selectivity, can be enhanced simultaneously. Abstract : Although PEBAX-1657 is one of the promising polymeric materials for selective CO2 separation, there remain many questions about the optimal polymeric structure and possibility of improving performance without adulterating its basic structure by impregnating inorganic fillers. In order to improve the gas separation performance, low thickness PEBAX membranes were synthesized under steady solvent evaporation conditions by keeping in mind that one of its segments (nylon 6) shows structural variance and molecular orientation with a change in the evaporation rate. Furthermore, phase pure zeolite nanocrystals with cubic (zeolite A) and octahedral (zeolite Y) shapes have been synthesized through liquid phase routes using microwave hydrothermal reactors. The average sizes of zeolite A and Y crystals are around 55 and 40 nm, respectively. The inspection of XRD, DSC and Raman shift of PEBAX membranes demonstrates the formation of a stable polymeric structure with an improved crystalline state which results in high CO2 permeability membranes. The CO2 permeability as well as diffusivity increase with a decrease in membrane thickness and reach a maximum value of 184.7 Barrer and 2.6 × 10 −6 cm 2 s −1, respectively. The as-fabricated pristine PEBAX membrane shows much better performance in terms of permeance (CO2 184.7 Barrer), diffusivity (CO2 2.6 × 10 −6 cm 2 s −1 ) and selectivity (CO2 /N2 59.7), which substantiate its promising prospects for CO2 capture. This exceptional performance of the pristine PEBAX membrane arises from the free volume generated during the steady polymerization. This reported approach for PEBAX membrane synthesis provides a direction in the design of membrane fabrication processes for economic CO2 separation.